Simulation of Biomechanical Behaviour of Polymeric Prothestic Foot and Performace Improvent by Topology Optimization - علي, فادي (Latakia University Journal -Engineering Sciences Series, 2020)
Based on the importance of biomimetics in the design of prostheses, especially the foot, this study presents a numerical simulation of biomechanical behavior with the aim of improving the performance of polymeric prosthetic foot.The 3D model of prosthetic foot is created by capturing two-dimensional profiles of foot based on ordinary photographs. Dynamic B-Spline curves are used to plot aacuratly the two-dimensional sketchs of trace of foot. Numerical analysis is carried out using the finite elements to test the performance of the foot made of polymeric materials in three different positions of walking. Numerical results show that the use of polymeric materials for prosthetic foot with biomimetics shape of real human foot leads to dynamic distribution of stresses corresponding to the different positions of the foot in walking, which improves the kenimatic performance of prosthetic foot user. The addition of toplogy modifications to the design of prosthetic foot clearly leads to weight loss as well as improved energy storage in the foot by increasing the elastic deformability. On the other hand, the shape, dimensions and position of topological modifications should be carefully chosen to minimize the appearance of stress concentrations in the material.